Лигнин как индикатор среды осадконакопления на арктическом шельфе; Доклады Академии наук; Т. 467, № 1 - Ульянцев А. С. Александр Сергеевич; Романкевич Е. А. Евгений Александрович; Пересыпкин В. И. Валерий Иванович; Беляев Н. А. Николай Александрович; Семилетов И. П. Игорь Петрович; Братская С. Ю.; Ветров А. А.; Сергиенко В. И. Валентин Иванович (2016, 2016)
Заглавие с экрана